PROVERBS AND SAYINGS IN CHINESE (Scientific journal of the Fergana State University, 2023)
The following article will give the importance of Chinese didactic folklore: proverbs and sayings, as well as their pronunciation and translations. This feature shows how relevant and interesting the article. Proverbs and sayings are considered a genre of folk art, consisting of short and concise, figurative and non-figurative, grammatically and logically complete wise expressions. Learning this genre is always a challenge. Pronunciation and translations of proverbs and sayings in this article will help language learners.